(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Abstract: Millions of people all over the world are affected by disability arising out of accident, disease, or congenital. This is a crucial health issue for mankind and needs structured treatment and rehabilitation plans. Prevalence and management capacity of disability have wide cross-cultural and geographical variations. Despite the lack of specific data there are reasons to believe that third-world countries have more disabilities and fewer resources and capacity for rehabilitation. So, there is a strong relationship between poverty and disability. Marginalized populations, disadvantaged or at-risk populations such as women, older people, and people who are poor are inappropriately affected by disability. Children from poverty-stricken families, indigenous populations, and ethnic minority groups are significantly at higher risk of experiencing disability. There is a higher prevalence of disability in lower-income countries than in higher-income countries. Poor people from lower-income countries are usually involved in high-risk jobs which make them vulnerable to injury and disability. Because of exaggerated life stress, poor health status, and poor living conditions due to poverty, people at low resource outset are more vulnerable to disease and disability. Of inadequate support from affluent persons as well as from the government, they spend their last savings to meet the treatment costs and get poorer. They are also common victims of road traffic accidents when they travel on risky roads and vehicles. There are many other shreds of evidence for a link between disability and poverty in low and middle-income countries and there is an urgent need for further research and policy action to break the cycle. This review article intends to find out the relationship between poverty and disability and reveals how poverty influences suffering disability and vice versa. J Bangladesh Coll Phys Surg 2024; 42: 63-67